A Second Look at the Pesticides Initiative Program : Evidence from Senegal - Jaud, Melise; Cadot, Olivier (2012)
This paper investigates whether the Pesticides Initiative Program has significantly affected the export performance of Senegal' shorticulture industry. The authors apply two main microeconometric techniques, difference-in-differences and matching difference-in-differences, to identify the effect of the Pesticides Initiative Program on exports of fresh fruits and vegetables. They use a unique firm-level dataset containing data on sales, employment, and exports by product and destination markets, as well as firm enrolment year, over 2000-2008. The results suggest that wile the program had no significant effect on exports pooled over all products and destinations, it had a positive effect when considering fresh fruits and vegetables exports to the European Union.